Analysis of Factors Influencing Mechanical Properties of Recycled Polypropylene/Tea Waste Composites Using Factorial Experimental Design - Khongrit, Anuchit; Limsiri, Cheevin; Meehom, Sureeporn (Journal of Advanced Development in Engineering and Science, 2026)
This study aimed to analyze the influence of key factors on the mechanical properties of recycled polypropylene/tea waste composites using a General Factorial Design experiment. The research evaluated the effects of tea waste type (Thai tea and green tea), polypropylene- graft-maleic anhydride (PP-g-MA) content, and thermoplastic elastomer (TPE) content on yield strength, tensile strength, elastic modulus, elongation percentage, impact strength, and hardness. Analysis of Variance (ANOVA) and quantitative effect analysis revealed that all three factors had statistically significant impacts on the composites’ mechanical properties. Specifically, tea waste type significantly influenced hardness and elastic modulus, while PP-g-MA positively affected the yield strength, tensile strength and elastic modulus, and TPE enhanced impact strength and elongation percentage. The contour plot analysis provided insights into the relationship between factors and mechanical properties, aligning with the main effects analysis results. No significant interactions were found between tea waste types and PP-g-MA or TPE content for most mechanical properties, except for elastic modulus and hardness. Regression coefficient analysis and linear regression for mechanical properties prediction showed moderate predictive capability, with determination coefficients ranging from 47.29% to 67.77%. Using the desirability function optimization method, the formulation containing green tea waste and 5% PP-g-MA without TPE achieved the highest composite desirability of 0.90, indicating the best balance of mechanical properties. Although adding 5% TPE significantly improved impact resistance and elongation percentage, it reduced the maximum tensile strength. This research suggests that the material is suitable for applications not requiring high strength, making it appropriate for furniture manufacturing or home decoration such as garden and landscape decoration, wall or ceiling panels, and shelves or storage cabinets with light load-bearing requirements.